2015
DOI: 10.1515/pce-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards the Government’s Remembrance Policy in Poland: Results of an Experimental Study

Abstract: The paper presents the results of an experimental study of Polish students’ attitudes towards their government’s remembrance policy (or, in other words, the intentional narration and interpretation of the past by the government). It includes four parts: a justification of why remembrance is a significant political asset in post-Communist Poland; a classification of remembrance policy instruments; a presentation of general results of the study; and a discussion of participants’ attitudes to particular policy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…In general, participants who scored high in the collective remembrance tended to experience weaker attitude change than participants less interested in the issue. It confirms the results of our previous research, which suggested the instability of high support for collective remembrance over time (Wawrzyński & Schattkowsky, 2015). However, the negative effect was more substantial when participants were assigned to watch emotional stories.…”
Section: Pride and Compassion: How Emotional Strategies Target Audien...supporting
confidence: 90%
“…In general, participants who scored high in the collective remembrance tended to experience weaker attitude change than participants less interested in the issue. It confirms the results of our previous research, which suggested the instability of high support for collective remembrance over time (Wawrzyński & Schattkowsky, 2015). However, the negative effect was more substantial when participants were assigned to watch emotional stories.…”
Section: Pride and Compassion: How Emotional Strategies Target Audien...supporting
confidence: 90%
“…(Kaufmann, Kraay and Zoido-Lobatón, 1999) [128] . According to International Monetary Fund (2005) [129] , "Good Governance ensures rules of law, improves the effectiveness and accountability of the public sector, and performs the fight against corruption" (Saparniene & Valukonyte, 2012) [130] . It is competent management of a country's resources and affairs in an open, transparent, accountable, equitable, and responsive manner to the needs of citizens (Johnston, 2004) [44] .…”
Section: Good Governance: a Paradigm Shiftmentioning
confidence: 99%